THE IMPLEMENTATION OF 10TH ECONOMIC POLICY PACKAGE RELATED SMALL MEDIUM ENTERPRISES ESTABLISHMENT IN INDONESIA - Putra, Gratianus Prikasetya; Gumay, Panji Satria (Jurnal Ekonomi dan Pembangunan, 2019)
Small Medium Enterprises company is one of the most popular business entities today. The popularity is cannot be separated from the spirit of entrepreneurship with young creative mindset that become mainstream in daily life. In relevancy with that, The Government of Republic Indonesia enacted Government Regulation No 29 Year 2016 to simplify the establishment process of Small Medium Enterprises legal entity. In practice area, the enactment of that regulation cannot be implemented well because there are some miss connections in regulations structure of Indonesia. In order to solve the problem, this research uses the normative research methodology that possible to answer by describing and explaining the facts with the applied regulation. The theory of limited liability company based on Indonesian Law such as Law No 40 Year 2007 was also applied in this research as a tool to analyse and solve the problem related that issue.